Pengaruh Disiplin Kerja, Pelatihan Kerja dan Efikasi Diri Terhadap Kinerja Karyawan Pada Dapartemen Engineering Hotel Hanging Gardens Of Bali - Ni Made Satya Utami; Ary Wira Andika; Ni Kadek Ira Darmayanti (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Employee performance is one of the keys to a company's success in achieving success. Employee performance is influenced by many things such as work discipline, job training and self-efficacy. This research aims to determine the influence of work discipline, work training and self-efficacy on employee performance in the engineering department of the Hanging Gardens Of Bali Hotel. The population in this study was all 36 employees of the Hanging Gardens Of Bali Hotel engineering department. The type of data used in this research is quantitative. Determining the number of samples using a saturated sampling technique with a sample size of 36 employees. The data analysis technique used is multiple linear regression analysis, F test, t test assisted by the SPSS version 25 program. From the research results, it was found that work discipline had a positive and significant effect on employee performance, work training had a positive and significant effect on employee performance, and self-efficacy. has a positive and significant effect on employee performance.